Clinical Outcomes of COVID-19 Convalescent Plasma According to Treatment Timing and ELISA Antibody Levels: A Real-World Retrospective Cohort Study - Özlem Bayraktar Saral; Ayla Yavuz; Şenol Ardıç; Tuncay Yazıcı; Serap Özer Yaman (Medicina, 2026)
Background and Objectives: Convalescent plasma (CP) was widely used during the early phase of the COVID-19 pandemic; however, evidence regarding its clinical benefit has remained inconsistent. This study evaluated the associations of CP administration timing and the ELISA antibody level of the transfused unit with clinical outcomes among patients with COVID-19. Materials and Methods: This retrospective real-world cohort study included 272 adults with RT-PCR-confirmed COVID-19 who received a single CP unit at the University of Health Sciences Trabzon Kanuni Training and Research Hospital, Türkiye, between 1 April 2020 and 1 April 2021. At CP administration, 180 patients were hospitalized, and 92 were treated as outpatients; initial cohort assignment was retained throughout follow-up. Anti-SARS-CoV-2 IgG was assessed using the semi-quantitative Euroimmun ELISA, and exploratory low (0.00–0.99), medium (1.00–4.99), and high (≥5.00) categories were used. The primary outcome was 30-day all-cause mortality. Results: During follow-up, 18 of 92 outpatients (19.6%) required hospitalization. Thirty-day mortality was higher among hospitalized patients than among outpatients (39.4% vs. 1.1%; p < 0.001), reflecting major baseline clinical differences between the groups. Median ELISA indices did not differ significantly between hospitalized patients and outpatients [4.23 (IQR, 2.65–6.43) vs. 3.64 (IQR, 2.16–6.13); p = 0.308]. Among hospitalized patients, ELISA-index distributions were similar between survivors and non-survivors (p = 0.427), and the index was not associated with mortality when analyzed continuously after log2 transformation (OR per doubling, 0.89; 95% CI, 0.67–1.19; p = 0.425). The high-versus-medium category comparison was also non-significant (OR, 0.88; 95% CI, 0.48–1.62; p = 0.757), as was the timing-by-ELISA interaction (p = 0.074). Conclusions: In this CP-treated cohort, the ELISA index of the transfused unit was not independently associated with 30-day mortality. The exploratory subgroup findings do not establish CP effectiveness or superiority of a particular timing or antibody-level category.